ASSESSMENT OF HEAVY METAL CONTAMINATION IN WATER, SOIL, AND FEATHERS OF Bubulcus ibis IN CANAL ECOSYSTEMS OF PAKPATTAN, PUNJAB, PAKISTAN - Waseem Akram; Khalid Mahmood Anjum; Nawal Tabassum; Hadia Liaqat; Rubia Afzal; Azeem Ali; Atif Yaqub (Journal of Animal and Plant Sciences, 2026)
Environmental contamination by heavy metals is a leading concern, particularly in aquatic ecosystems where pollutants can accumulate and disrupt ecosystem balance. This study evaluates the presence of manganese (Mn), lead (Pb), copper (Cu), and zinc (Zn) in water, soil, and Bubulcus ibis (cattle egret) feathers collected from selected sites in Pakpattan, Punjab, Pakistan. 24 samples comprising (8 soil, 8 water, 8 avian) feathers were obtained from four canal locations. Heavy metal concentrations were analyzed by atomic absorption spectrophotometry, with measured concentrations in samples as follows: Mn (water: 19.56±4.01, soil: 14.01±5.60, feathers: 2.06±0.53), Pb (water: 7.97±1.62, soil: 11.81±1.51, feathers: 10.30±1.57), Cu (water: 7.43±1.04, soil: 6.75±1.16, feathers: 3.09±0.59), and Zn (water: 0.62±0.21, soil: 2.34±0.76, feathers: 7.18±1.32).Results showed significant differences (p < 0.05) in concentrations across media for Mn, Cu, and Zn: Zn accumulated predominantly in feathers, while Mn and Cu were highest in water and soil. Pb showed no significant variation (p = 0.244). Correlation analysis revealed possible contamination sources and pathways affecting metal distribution. These findings highlight the potential of avian feathers as bio-indicators for monitoring heavy metal pollution and emphasize the necessity for ongoing environmental assessment and conservation efforts.
Keywords: orange; postharvest; packaging; plastic materials; darkness; storage; shelf life; quality; enzymes; Water; Soil; Cattle egret; Heavy metals; feathers